Recombinant antibody production by cloning of Pepper yellow leaf curl Indonesia virus (PepYLCIV) coat protein gene - Yashanti Berlinda Paradisa; Sri Sulandari; Sedyo Hartono; Susamto Somowiyarjo; Mery Windarningsih; Dini Wahyu Kartika Sari; Christina Retna Handayani (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2022)
Pepper yellow leaf curl Indonesia virus (PepYLCIV) is an important pathogen on chili cultivation and is transmitted through the seed. Serological tests are sensitive, accurate, efficient and it has been widely used for the detection of seed-transmitted plant viruses. This study aimed to produce PepYLCIV recombinant protein as a material to produce recombinant antibodies PepYLCIV. DNA was extracted from infected chili leaves collected from Congkrang, Muntilan, Central Java verified using primer PepYLCIV-BamHI and PepYLCIV-EcoRI and produced an amplicon at 840 bp. The amplified fragments were cloned into the pET32a then transformed to Escherichia coli BL21. The percentage of nucleotide sequence identity and sequence of amino acid, PepYLCIV CK-6 isolates had the highest similarity of nucleotide and amino acid sequences to of chili isolates from Bandung. The expressed recombinant protein was obtained with IPTG concentration 0,5 mM and harvested at 6 hours after IPTG induction. SDS PAGE analysis of the recombinant plasmid Begomovirus CK-6 showed that the coat protein size was about 29 kDa. Immunization was carried out on rabbits by injecting 150 µg of recombinant protein 4 times with an interval of 1 week to produce crude antiserum and pure antiserum capable of detecting PepYLCIV in chili and Ageratum conyzoides using I-ELISA and DIBA tests.